A novel reactive chemosensor for sulfide detection with high selectivity and sensitivity based on 4-Cl coumarin derivatives. (July 2021) - Li, Hongda; Yang, Yunfan; Wu, Xiaojing; Jia, Rulin; Zhao, Pengcheng; Wang, Yan
Abstract: We describe the design and synthesis of a novel reactive chemosensor based on 4-Cl Coumarin derivatives. This chemosensor displays significantly fluorescence performance in the detection of sulfur ions in water samples, and the inactive mechanism has been clearly demonstrated via fluorescence titration, Job's plot, ESI-MS, 1 H NMR and Quantum chemistry calculation. Graphical abstract: Image 1 Highlights: A new reaction chemosensor for S 2− based on 4-Cl Coumarin derivatives. The reactive mechanism was confirmed by fluorescence titration, ESI-MS, 1 H NMR and Quantum chemistry calculation. The chemosensor for S 2− displays good selectivity, fast response speed, high sensitivity and easy operation. The chemosensor 1 for S 2− showed a linear correlation, and LOD was calculated as 0.12 μmol/L. The visual test paper, colorimetric card and inspection process were designed for the detection of S 2− .